Legal Protection of Local Product of Kopi Tambora as A Product of Geographical Indications in West Nusa Tenggara Province - Ika Saputri; Taufik Firmanto; I Ilyas; Z Zuhrah; E Erham; Ainun Wulandari (Universitas Muhammadiyah Surakarta, 2023)
Introduction, This article is a legal research that discusses the legal protection of local Kopi Tambora products as a product of geographical indications in the province of West Nusa Tenggara. The methods used in this study are normative legal research methods, with several approaches used, namely, the statutory approach, the concept approach, the historical approach, and the analytical approach. Novelty, from this research it was found that the efforts to protect the law against the local Kopi Tambora product as a geographical indication product by the West Nusa Tenggara Province government had not been optimal. Result & Discussion , from this study it was found that the legal protection efforts for the local Kopi Tambora product as a product of geographical indications by the West Nusa Tenggara Provincial government were not optimal. The NTB regional government needs to pay attention to and increase supervision of the legal protection of geographical indications for Kopi Tambora in order to maintain the uniqueness of local products as a regional identity so as to avoid claims by other regions for local Kopi Tambora products to be able to compete nationally and internationally. Conclision, that the legal protection for local Kopi Tambora products as a product of geographical indications in West Nusa Tenggara Province is not optimal. The lack of attention and supervision by the local government in protecting local products as a geographical indication does not rule out the possibility that Kopi Tambora that has been registered with the Directorate General of Intellectual Property (DJKI) may have its protection removed as a geographical indication. Supervision from the local government on legal protection for local Kopi Tambora products as a geographical indication will make Kopi Tambora a product that is not only worth selling at the regional level but can also compete in national to international markets so that it can increase MSME income and regional income.